Numerical and experimental analysis of effect of working fluid amount on the thermal performance of thermo-syphon system. Issue 2 (November 2020) - Jasim, Ayoob Khalid; Freegah, Basim; Alhamdo, Mohammed Hamed
Abstract: The thermal performance enhancement of a thermo-syphon system has been studied by many researchers. However, according to the best knowledge of the authors, the impact of the amount of the working fluid on the performance of thermo-syphon has not hitherto been studied. In the present work the impact of inserting a closed tube inside the riser pipe and effect of increase and decrease the amount of the working fluid on the thermal performance have been investigated. Several cases have been considered and tested. To ensure the validity of the theoretical results, an experimental work has been conducted and results compared with numerical results. The results show good match between numerical and experimental results. In particular, the maximum difference between experimental and numerical results is found 14.52% and 11.23% for water temperature inside tank and working fluid at outlet of the riser pipe respectively. As well as, the numerical results have been demonstrated that the amount of the working fluid within the thermos-syphon loop has a noticeable impact on the thermal performance of the regarding system. Furthermore, it is found that the (case-A-) is the best case among all cases under consideration regarding system the thermal performance of thermos-syphon. Moreover, a correlation equation to predict water temperature within the storage tank has been established. The accuracy of this equation around 95.6%.